Coupling coordination and spatial-temporal characteristics of resource and environmental carrying capacity and high-quality development - Li, Zhi; Chen, Ying; Zhang, Liuyue; Wang, Wenju; Wu, Jie (Frontiers in Environmental Science, 2022)
The high-quality development of society needs the support of resource and environmental carrying capacity, and the improvement of resource and environmental carrying capacity is driven by the process of high-quality development. Therefore, how to realize the dynamic coordination of the two is an urgent problem to be solved. Based on the panel data of 30 provinces in China from 2005 to 2020, this paper uses the information entropy method, coupling coordination degree and kernel density estimation model to explore the coupling coordination relationship and spatial-temporal characteristics between resource and environmental carrying capacity and high-quality development. The results show that there are four nonlinear relationships between resource and environmental carrying capacity and high-quality development, including simultaneous increase, first increase and then decrease, first decrease and then increase, and alternating fluctuation; Water resources per capita and green coverage rate of built-up area contributed the most to the resource and environmental carrying capacity subsystem, and GDP per capita and urbanization rate contributed the most to the high-quality development subsystem. From the time series, the coupling relationship between the two shows an upward trend over time. From the spatial series, the coupling relationship between the two is in a state of spatial aggregation. Finally, this paper discusses the results and puts forward policy recommendations, hoping to provide reference for the coordinated development of the region.